High Resolution Patterning of an Organic–Inorganic Photoresin for the Fabrication of Platinum Microstructures. Issue 37 (1st August 2021) - Luitz, Manuel; Lunzer, Markus; Goralczyk, Andreas; Mader, Markus; Bhagwat, Sagar; Warmbold, Andreas; Helmer, Dorothea; Kotz, Frederik; Rapp, Bastian E.
Abstract: Platinum (Pt) is an interesting material for many applications due to its high chemical resilience, outstanding catalytic activity, high electrical conductivity, and high melting point. However, microstructuring and especially 3D microstructuring of platinum is a complex process, based on expensive and specialized equipment often suffering from very slow processing speeds. In this work, organic–inorganic photoresins, which can be structured using direct optical lithography as well as two‐photon lithography (TPL) with submicrometer resolution and high‐throughput is presented. The printed structures are subsequently converted to high‐purity platinum using thermal debinding of the binder and reduction of the salt. With this technique, complex 3D structures with a 3D resolution of 300 nm were fabricated. At a layer thickness of 35 nm, the patterns reach a high conductivity of 67% compared to bulk platinum. Microheaters, thermocouple sensors as well as a Lab‐on‐a‐Chip system are presented as exemplary applications. This technology will enable a broad range of application from electronics, sensing and heating elements to 3D photonics and metamaterials. Abstract : High‐resolution patterning of an organic–inorganic platinum containing photoresin by microlithography and two‐photon polymerization is demonstrated. The polymerized microstructures are debinded and reduced to highly conductive metallic platinum at a resolution of 300 nm. The conductivity of the reduced platinum structures is 67% of the conductivity of bulk platinum.